A Partial Equilibrium Model for Future Outlooks on Major Cereals in India - Parappurathu, Shinoj; Kumar, Anjani; Kumar, Shiv; Jain, Rajni (SAGE Publications, 2014)
A far-sighted food policy is essential to facilitate efficient functioning of food production and management systems, especially for a country like India where household level food security still remains elusive. In this context, reliable mechanisms for generating outlooks on key variables such as demand, supply, trade, prices, etc., of important food commodities forms an essential basis for planning. This paper explores the theoretical underpinnings as well as practical applications of the Cereal Outlook Model, a dynamic, partial-equilibrium model, developed by the authors with the specific purpose of generating future outlooks on major cereals in India. Based on this, projections as well as policy simulations on main demand and supply side variables of rice, wheat and maize were carried out for the period spanning 2011–2025. The model results indicate fast-growing trends in demand and supply of the three cereals considered. Though growth in demand would be sufficiently high due to growing per capita income, population and urbanisation; supply would keep pace owing to the emergence of new areas contributing towards incremental production. Consequently, the net trade of all three commodities would remain positive, though some signs of tapering off in net trade are expected in case of wheat and maize.JEL Classification: Q18, Q11, C5